2022
DOI: 10.2196/34984
|View full text |Cite
|
Sign up to set email alerts
|

Well-being of Canadian Armed Forces Veterans and Spouses of Veterans During the COVID-19 Pandemic: Protocol for a Prospective Longitudinal Survey

Abstract: Background The COVID-19 pandemic has resulted in significant changes to everyday life, including social distancing mandates, changes to health care, and a heightened risk of infection. Previous research has shown that Canadian Armed Forces (CAF) veterans are at higher risk of developing mental and physical health conditions. Veterans and their families may face unique social challenges that can compound with pandemic-related disruptions to negatively impact well-being. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Given the sporadic distribution of labels, the utilization of clustering techniques to group the Brief MIOS scores would be optimal for effective data processing and classification. As mentioned previously, the Brief MIOS is yet to have established severity cut-off scores [17] , [44] , therefore clustering was necessary to group the participants’ Brief MIOS scores. During the clustering phase, we used -means clustering.…”
Section: Resultsmentioning
confidence: 99%
“…Given the sporadic distribution of labels, the utilization of clustering techniques to group the Brief MIOS scores would be optimal for effective data processing and classification. As mentioned previously, the Brief MIOS is yet to have established severity cut-off scores [17] , [44] , therefore clustering was necessary to group the participants’ Brief MIOS scores. During the clustering phase, we used -means clustering.…”
Section: Resultsmentioning
confidence: 99%
“…A national longitudinal online survey was distributed across Canada to English- and French-speaking CAF Veterans and spouses/partners of Veterans (see Forchuk et al [ 22 ] for specifics around study design). Participants were recruited using professional networks, social media advertisements, participant recruitment websites, press releases, Veteran community and advocacy groups, and word of mouth.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were not offered remuneration for study participation. The spousal baseline data drawn from this large longitudinal study [ 22 ] serves as the data source for the current study. Results from a previous study of Veterans using identical sampling methods [ 12 ] found that 77% of Veterans reported being married/in a relationship.…”
Section: Methodsmentioning
confidence: 99%
“…Data were drawn from the primary baseline data of a longitudinal survey examining the psychological functioning of Canadian veterans during the COVID-19 pandemic 25. For further details on methodology, please see Forchuk et al 25.…”
Section: Methodsmentioning
confidence: 99%
“…Data were drawn from the primary baseline data of a longitudinal survey examining the psychological functioning of Canadian veterans during the COVID-19 pandemic 25. For further details on methodology, please see Forchuk et al 25. Data from those who identified as Canadian veterans (ie, had served in the Canadian Armed Forces and had released prior to survey completion) who completed the baseline survey (from July 2020 to February 2021) were included in the present study.…”
Section: Methodsmentioning
confidence: 99%